Parental COVID‐19–related health information practises, sources, evaluations and needs: A qualitative interview study. (8th December 2022) - Altawil, Hala; Klawunn, Ronny; Dierks, Marie‐Luise; Lander, Jonas
Abstract: Background: Parents of infants and young children may have specific health information needs and preferences, as they are responsible for their children's health. COVID‐19 posed many challenges for families, not least in terms of the constantly updated disease‐prevention guidelines. However, little is known about parents' experiences with this unprecedented situation, that is, how and where they seek, use and evaluate COVID‐19 (child)‐specific health information. We aimed to find out more about this to provide insights to health (information) providers when communicating pandemic information to parents. Methods: We conducted semistructured telephone interviews (August to October 2020) with a purposively selected sample of 20 German‐speaking and 10 Arabic‐speaking parents of children up to 4 years old. Recruitment occurred through multiple channels, including childcare institutions and social media. Qualitative content analysis of the interview transcripts illustrates the main differences between the two groups. Results: By the time the interviews were conducted (mid‐2020), some parents reported to seek information less actively or not at all, compared to the beginning of COVID‐19. German speakers frequently used Google to obtain information, whereas Arabic speakers mentioned social media (particularly Facebook) as a central source. However, medical providers were the most trusted source for child health. Though determining the credibility of online information was difficult for some parents, others, mostly German speakers (middle–high education), were aware of some author‐related criteria. When deciding on information use, parents often rely on their own judgement and gut instinct. Besides the necessity to disseminate information via multiple outlets to reach all parents, Arabic speakers desired audio‐visual and translation tools to facilitate understanding. Discussion and Public Conclusion: Apart from education, language and knowledge of the health system and of the attributes of credible information may determine its quality and consequent decisions. There seems to be a considerable need to foster knowledge about reliable information sources, a greater understanding of the range of quality criteria and specific support for nonnative speakers, not least to better inform parents' decision‐making. Patient and Public Contribution: A parent panel ( n  = 7) contributed to gathering ideas regarding recruitment, discussing initial results and the choice of topics and questions for a second interview phase.